The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/geosciences9020093
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium as an Emerging Microcontaminant in Water Resources: Threats and Opportunities

Abstract: As a result of high doses of paramagnetic gadolinium (Gd) chelates administered in magnetic resonance imaging (MRI) exams, their unmetabolized excretion, and insufficient removal in wastewater treatment plants (WWTPs), large amounts of anthropogenic Gd (Gdanth) are released into surface water. The upward trend of gadolinium-based contrast agent (Gd-CA) administrations is expected to continue growing and consequently higher and higher anthropogenic Gd concentrations are annually recorded in water resources, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 191 publications
(336 reference statements)
1
40
0
Order By: Relevance
“…Only two species of microalgae have been tested for the removal of the indigo blue (Spirulina platensis here and Scenedesmus quadricauda [15]). Both were able to achieve removals between 90% and 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two species of microalgae have been tested for the removal of the indigo blue (Spirulina platensis here and Scenedesmus quadricauda [15]). Both were able to achieve removals between 90% and 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent progress has been made in an integrated perspective of wastewater treatment that includes standard and biological technologies for pharmaceutical emerging contaminants [4][5][6][7], industrial chemicals [8,9], brewery wastewater [10], agro-industrial wastewater [11,12], heavy metals [13,14], and emerging compounds [15].…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] In recent years, utilization of high technology metals such as rare earth elements (REEs), whose abundance are extremely low in the earth, has rapidly increased with development of new types of industrial materials and pharmaceutical products. 38,39 In pollution may occur. Thus, we became interested in the research for a new type of potential anthropogenic pollution of high-technology metals with a focus on REEs in environmental water.…”
Section: Introductionmentioning
confidence: 99%
“…Eu and Tb. 15,39, This was artificially caused by anthropogenic sources mainly due to use of Gd compounds used as a contrast reagent for magnetic resonance imaging (MRI) in medical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Even if Gd is mainly transported as a dissolved fraction (Kulaksiz and Bau, 2013), according to Migaszewski and Gałuszka (2015) the origin and mechanisms of controlling the LREE, MREE, or HREE enrichment in soluble and solid fractions are still unknown. It is particularly unclear whether the REE patterns are linked to the aqueous processes or are related to the source of these elements (Ebrahimi and Barbieri, 2019). In recent reviews, Rogowska et al (2018) reported the scarcity of information on the level of Gd in aquatic sediments and the lack of any speciation analysis (China, Australia, Europe) and Migaszewski and Gałuszka et al (2015) highlighted the need to improve our knowledge about behaviour and origin of REE in the environment.…”
Section: Introductionmentioning
confidence: 99%